Pengaruh Persepsi Siswa tentang Metode Mengajar Guru tehadap Prestasi Belajar Khat Imlak - Iis Makhisoh (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
This study aimed to determine the effect of students 'perceptions of teachers' teaching methods and motivation to increase student achievement khat imlak class IIA Bahr Ulum Madrasa Mu'allimin Mu'allimat Tambakberas Jombang. To analyze this research using quantitative methods. In this quantitative study is to obtain data using questionnaires and documentation. As many as 123 student population, 30% of samples taken her to 37 students. Hypothesis testing consists of simple regression, and multiple regression The results of this study show that: 1. a positive and significant impact on students 'perceptions of teachers' methods of teaching handwriting imlak learning achievement and motivation to learn, 2. a positive and significant impact on learning achievement motivation khat imlak, 3. a positive and significant impact on students 'perceptions of teachers' methods of teaching and learning motivation together khat imlak learning achievement and motivation to learn.